A practical offer for hypospadias dressing: Allevyn® - Adnan Narci; Didem Baskin Embleton; Evrim Özkaraca Boyaci; Serdar Mingir; Salih Çetinkursun (Wolters Kluwer Medknow Publications, 2011)
Introduction: An ideal hypospadias dressing material must be cheap and non-allergenic. It also must be easily and quickly applied, non-adherent to the incision, effectively absorb the leakages of the wound, pressurise the flaps and grafts effectively, without damaging the blood circulation, protect against infections, and must be easily and painlessly removable. We use a product that is produced for healing chronic wounds and burns, Allevyn Adhesive® , as a wound dressing after hypospadias surgery and circumcision. Materials and Methods: We included 61 hypospadias and 85 circumcision cases operated in our clinic between November 2007 and August 2010, for the study. Allevyn Adhesive® dressing was used in all the cases. For approximately every 10 patients a sheet sized 22.5 x 22.5 cm was used. Results: We did not meet any difficulty in application and removal of the dressings and the dressing could be performed easily even by inexperienced health personnel. The cost of the application is about $5 for each case. We did not encounter any complications with regard to the dressing during the follow-up. Conclusion: We did not encounter any of the complications with Allevyn Adhesive® that were seen with the use of traditional dressing products, such as, problems with removal of the dressing, development of maceration secondary to inadequate absorption of leakages from the wound, cohesions of the wound lips, and infections and necrosis of the flaps and grafts, secondary to erroneous locations of the dressings. There was no additional therapeutical cost due to the use of this product. For these reasons we thought that Allevyn Adhesive® is a good alternative for the dressing of hypospadias and circumcision.